Stabilization Appliance for Masticatory Pain Secondary to Bruxism: A Case report - Paudel, Sandhya; Suwal, P; Singh, RK; Parajuli, P; Limbu, IK; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2019)
Occlusal appliance therapy is a proven modality for facilitating diagnosis and alleviating the pain related to different types of temporomandibular dysfunctions and obnoxious par functional habits such as bruxism and clenching. A properly fabricated occlusal appliance or splint serves the functions of relaxing the masticatory muscles, allowing the condyle to seat in centric relation, providing diagnosticinformation, protecting teeth and associated structures. The stabilization appliance has shown to decrease par functional activity thus considered when pain occurs due to muscle hyperactivity due tobruxism. This case report highlights on the management of masticatory pain secondary to bruxism with stabilization appliance as an adjunct to other pharmacological and physical therapy. A heat cured acrylic stabilization appliance was fabricated and delivered to the patient which significantly reduced the pain within four weeks.